The Self-Efficacy of Preservice Teachers in STEM Pedagogical Content Knowledge (London Journal of Research In Humanities and Social Sciences, 2023)
STEM education is a useful tool in promoting 21st-century competencies, such as cultural awareness, critical-thinking and problem-solving skills. Having these skills prepares students for a competitive, global marketplace. Teachers play a crucial role in providing quality STEM education, and teachers require high levels of self-efficacy and STEM pedagogical content knowledge to impart quality levels of instruction. We examined the relationship between self-efficacy and STEM pedagogical content knowledge. Results showed higher self-efficacy was related to higher STEM pedagogical content knowledge. Implications are discussed.
Keywords: stem education; preservice teachers; self-efficacy; stem pedagogical content knowledge